Additive and Subtractive Rapid Prototyping Techniques: A Comparative Analysis of FDM & CNC Processes - Neuenfeldt-Junior, Alvaro; Cheiram, Marlon; Eckhardt, Moacir; Scheuer, Cristiano; Siluk, Julio; Francescatto, Matheus (International Journal of Industrial Engineering and Management, 2021)
The present research addresses a comparative analysis among Additive (ARP) and Subtractive (SRP) rapid prototyping techniques, aiming to determine which approach presents greater technical and economic viability for physical prototype manufacturing. The Analytic Hierarchy Process (AHP) multi-criteria decision method was used to categorize and quantify the analysis criteria. The analyzed Rapid Prototyping (RP) techniques were the Computer Numerical Control (CNC) milling as SRP technique and the Fused Deposition Modeling (FDM) process as ARP. The SRP rapid prototyping technique is the most suitable alternative for manufacturing prototypes, according to the analyzed evaluation criteria. Article history: Received (April 20, 2021); Revised (August 9, 2021); Accepted (August 14, 2021); Published online (November 9, 2021)